2011
DOI: 10.1080/02673037.2011.593129
|View full text |Cite
|
Sign up to set email alerts
|

Who Experiences Foreclosures? The Characteristics of Households Experiencing a Foreclosure in Minneapolis, Minnesota

Abstract: Much of the existing research on disparities in residential foreclosures provides strong, but not conclusive, evidence that minority households disproportionately experience foreclosures. Data commonly used in foreclosure research do not allow researchers to use household characteristics of foreclosed properties to test for disparities in experiencing foreclosure. This is a significant omission in the literature since understanding the types of households that most typically experience foreclosure might result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…A remaining unexamined link is the connection between declines in voter turnout due to foreclosure and patterns of inequality in political disenfranchisement. Other research demonstrates associations among the socioeconomic status, race, and ethnicity of borrowers and their exposure to subprime lending (Bocian, Li, and Ernst, 2008;Li, 2011) and home foreclosure (Allen, 2011;Rugh and Massey, 2010). Female-headed households have also been particularly exposed (Dymski, Hernandez, and Mohanty, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A remaining unexamined link is the connection between declines in voter turnout due to foreclosure and patterns of inequality in political disenfranchisement. Other research demonstrates associations among the socioeconomic status, race, and ethnicity of borrowers and their exposure to subprime lending (Bocian, Li, and Ernst, 2008;Li, 2011) and home foreclosure (Allen, 2011;Rugh and Massey, 2010). Female-headed households have also been particularly exposed (Dymski, Hernandez, and Mohanty, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A research assistant who is a native Spanish speaker conducted eleven of the interviews in Spanish. While there is no national data available on immigrant foreclosure experiences, regional studies have identified foreign-born homeowners as at potentially greater risk for foreclosure than their native born counterparts (Allen 2011). I coded the transcribed interviews and field notes by identifying common themes and patterns throughout the interviews.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly in the United States, people of low socio-economic status experience the most frequent house foreclosures (Allen, 2011;Pollack & Lynch, 2009). It follows that the likelihood of experiencing negative financial outcomes may be largely explained by socio-economic differences, and to a comparatively smaller extent by individual differences in psychological factors (i.e.…”
Section: For Example In Greatmentioning
confidence: 99%